“Hva har romerne noen gang gjort for oss i Nord- Norge?” Om mulige forbindelser mellom Romerriket og det nordligste Norge - Ravnå, Per-Bjarne (Nordlit, 2014)
“What Have the Romans Ever Done for Us Here in North Norway?”: On Possible Connections Between the Roman Empire and Northernmost Norway. This article argues that scholars studying the early history of northern Norway should pay more attention to Roman history. Even if the geographical distances were long, there are clear signs of connections between inhabitants of northern Norway and the Roman world during the Roman era. In order to understand these connections scholars also need to study Roman history in its own right. To make this point the article investigates the possible Roman connections of a well-known warrior grave from Steigen (Nordland County, North Norway), dated to the middle of the third century CE. The investigation yields no stunning new discoveries, but aims to contribute to a broader and more well-founded understanding of the buried man and the experiences he might have had, as well as a cautious and informed view of broader connections between the North and the Roman world.
Keywords: Nordlige barbarer; germanske leiesoldater; Nord-Norge og Romerriket; Den romerske hæren; romersk påvirkning; krigergrav i Steigen; gallisk imperium; Nordnorsk romertid